The implementation of building information modeling in MACalaysian construction industry - Azmi, Nurshazriena (2019)
Building Information Modeling (BIM) is a new approach of construction design. It does not only facilitate the digital representation for designs but also provides all the necessary information for any project before it is constructed. Despite these advantages, the adoption of BIM in Malaysian construction is very low. Therefore, this study has been conducted to assess the current status of BIM implementation in Malaysian construction industry. This study investigated potential benefits together with barriers to implementations of BIM and proposing effective strategies for enhancing the BIM implementation in construction industry. The methodologies adopted for this study included literature review, interview with industry experts and questionnaire surveys. Findings of the study revealed that the rate of BIM implementation in construction industry is very low. Main functions of BIM are energy optimization of the building, functional simulations and model-based cost estimation (5D). Potential benefits of BIM are improving the management and operation, enhance work coordination and improve design quality. Major barriers to low level of BIM implementation are lack of demand from clients, lack of the financial ability for the small firms and lack of the awareness of BIM by stakeholders. Provision of trial software, training of construction staff and introducing of BIM in university curriculum are very effective strategies in enhancing the implementation of BIM.